Super-resolution optofluidic scanning microscopy - Mandracchia, Biagio (Lab Chip, 2021)
Optofluidics enables visualizing diverse anatomical and functional traits of single-cell specimens with new degrees of imaging capabilities. However, the current optofluidic microscopy systems suffer from either low resolution to reveal subcellular details or incompatibility with general microfluidic devices or operations. Here, we report optofluidic scanning microscopy (OSM) for super-resolution, live-cell imaging. The system exploits multi-focal excitation using the innate fluidic motion of the specimens, allowing for minimal instrumental complexity and full compatibility with various microfluidic configurations. The results present effective resolution doubling, optical sectioning and contrast enhancement. We anticipate the OSM system to offer a promising super-resolution optofluidic paradigm for miniaturization and different levels of integration at the chip scale.